Internet Positif di Lingkup Perusahaan dengan Metode Response Policy Zone - Irawan, Dedi; Fatoni, Fatoni; Suryayusra, Suryayusra (P3M Politeknik Negeri Banjarmasin, 2019)
The internet is one form of sophistication of information and communication technology. Internet allows someone to to get the needed information easily. Therefore, the internet is a very important thing that must be mastered and utilized as well as possible. Given the dangers that exist on the internet, like a double-edged knife, on the one hand the internet can be used for positive activities and on the other hand the internet can also be used for negative things. The purpose of the author to do this research to build a positive internet network at PT. Pertamina Ubeb Adera by filtering negative contents based on a list of 773 thousand negative content blocked on the trust + â„¢ Positif website by the Ministry of Communication and Information therefore internet resources can be used effectively and efficiently, By using methods action research as well as the response policy zone method, the author can build a positive internet in the scope of PT. Pertamina Ubeb Adera company.